헌법개정과 사회적 기본권 - 윤수정(YUN Soo Jeong) (법학연구, 2018)
인간의 존엄성을 보장하고 실현하는 것은 공동체가 추구하는 최고의가치와 이념이라고 할 수 있다. 그러므로 헌법에서 인간의 존엄성을 최고의 헌법적 가치이자 헌법을 구성하는 원리로 삼고 이를 실현하고자하는 것은 당연하다. 현대 헌법에서 인간의 존엄성은 개인의 자유와 더불어 사회적 기본권을 보장함으로써 실현된다고 할 수 있다. 우리 헌법도 이 점에 주목하여 사회적 기본권을 법제화하여 모든 국민에게 최소한의 사회경제적 동질성을 보장하고 이로써 사회통합을 실현하는 것을목표로 하고 있다. 그러나 일반적으로 사회적 기본권은 헌법에 목표가설정되어 있을 뿐 그 내용과 수준 및 실현의 방법론이 기본적으로 개방되어 있기 때문에, 입법을 통해 구체적으로 내용이 형성되기까지는 규범력을 갖기 어렵다. 사회적 기본권이 보장하고자 하는 영역에 대한 광범위한 사실조사와 다층적인 형량과정을 거쳐 입법이 이루어져야만 기본권의 내용이나 보장의 정도가 현실화되기 때문이다. 제헌 헌법 이후 지금까지 헌법개정에 관한 논의들은 대부분 정부형태, 대통령의 선출방법 및 임기 등과 관련하여 정치권을 중심으로 이루어졌으나, 2018년 헌법개정에 관한 논의에서는 지난 30년 동안 헌법개정이없었고, 그 동안 진행된 사회경제적 및 국민의식의 변화에 맞춰 개헌이이루어져야 한다는 점에 대해서는 공감대가 형성된 만큼, 정부형태를 비롯한 권력구조와 관련된 조항 이외에도 기본권 규정, 특히 사회양극화및 경제불평등과 같은 구조적인 사회문제를 해결하기 위한 사회적 기본권 강화를 위한 개헌 논의 역시 활발하게 이루어졌다. 문재인 대통령이발의한 헌법개정안에서도 사회적 기본권 규정에서 적정한 삶의 질을 유지할 수 있도록 사회보장을 받을 권리, 임신‧출산‧양육과 관련하여 국가의 지원을 받을 권리, 쾌적하고 안정적인 주거생활을 할 권리, 건강하게살 권리, 안전하게 살 권리 등을 신설하는 한편, 어린이와 청소년, 노인과 장애인 등 사회적 약자의 권리를 구체화하는 등 이러한 논의들이 충분히 반영되었다. 헌법개정은 시대의 변화에도 불구하고 헌법의 기능을 유지하고자 하는 목적이 가장 중요한 계기가 된다. 헌법의 해석과 구체화만으로는 더이상 헌법이 그 기능을 수행할 수 없을 때 비로소 헌법개정이 정당화된다. 그리고 헌법의 규범적 특성 및 이러한 헌법개정의 정당화 요소에 비추어 볼 때, 입법작용이 헌법을 보충할 수 있다. 특히, 사회적 기본권의구체적인 실현은 입법작용을 통해서 이루어지기 때문에, 입법작용이 헌법개정의 상당부분을 대체할 수 있으며, 적극적인 사법심사를 통해 이를자극하고 통제할 수 있다. 사회적 기본권이 갖는 불명확성, 실현방법의다원성, 그리고 현실환경에의 종속 등을 고려할 때, 헌법에서 사회적 기본권의 실현을 위해 구체화된 조문을 두는 것은 헌법이 화석화(化石化)되어 가변적인 사회적 상황과 문제를 신축성 있게 포섭하기 어려울 수 있다. 헌법에서 구체성의 정도가 강해질수록 헌법은 해석의 여지 대신에개정의 필요성만을 갖게 될 것이다. 결론적으로, 사회적 기본권이 확대되고 강조되어야 하는 현실적 필요성이 인정된다고 할지라도. 그 수단으로서의 (대통령의 헌법개정안과 같은) 구체성의 정도가 강한 헌법개정은 좀 더 신중을 기해야 할 것으로생각된다. The protection and fulfillment of human dignity would be the highest value and idea for the community. Thus, it is obvious for the Constitution to regard human dignity as the highest constitutional value and fundamental principal which should be fulfilled. In the modern Constitution human dignity together with individual freedom can be fulfilled by the protection of fundamental social rights. The objective of our Constitution is to fulfill social integration by protecting minimum social economic homogeneity with the legalization of fundamental social rights. However, only the objective of fundamental social rights are stated in the Constitution, basically leaving the level and methodology opened. Therefore, it cannot have a normative power unless the content is specifically developed. The content of the fundamental rights and the scope of protection can be fulfilled through extensive fact-finding and multi-layered balancing on the area which is protected by fundamental social rights. Since the first Constitution, debates on the amendment of the Constitution was mostly focused on government system, presidential selection and presidential term by the political parties. However, since there has not been an amendment for past 30 years, and due to the changes in socio-economic situation and public consciousness the debates on the amendment in the year 2018 discussed more on the fundamental rights, especially fundamental social rights to solve social distribution and economic inequality rather than government system and the power structure. According to the amendment proposal by the president Moon, regarding the debates above, fundamental social rights such as rights to social security for a quality of life, rights to national assistance on pregnancy·birth·child care, rights to adequate and stable housing, rights to healthy living and rights to safe living was newly introduced; rights for the socially vulnerable groups such as children, elderly and disabled are specified. Despite of the chronological changes, maintaining the function of the Constitution is the most crucial motivation for the amendment. Only when the Constitution cannot function through interpretation and specification can the amendment be justified. Regarding the normative characteristics and justification elements, legislation can supplement the Constitution. Especially, the fulfillment of fundamental social rights can be achieved by legislation. Thus, legislation can replace substantial part of the constitutional amendment. Regarding the ambiguity, pluralism in methods and dependency to reality, establishing specific provision in the Constitution to fulfill fundamental social rights can cause problems such as fossilization and cannot embrace flexible social situation and problems. As the Constitution become more specified, the need for amendment will increase. In conclusion, even if the practical need for the expansion and enrichment of fundamental social rights would be recognized, specific amendment (such as the presidential amendment proposal) should be handled carefully. KCI Citation Count: 2